Ceramic core with embedded cavity structure, preset cavity sandwich and preparation method of slurry of ceramic core
By using the preparation method of cavity sandwich slurry and pre-installed cavity sandwich, the problem of poor cavity roughness in the ceramic core is solved, and a higher smoothness and more efficient production process is achieved.
Patent Information
- Application Number
- CN202411274055.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, it is difficult to completely remove the metal core, resulting in the inner cavity of the ceramic core being rough and has poor smoothness.
The preparation method of cavity sandwich slurry and pre-installed cavity sandwich, including the slurry material components: polyethylene glycol, graphite powder, quartz glass powder and chopped nylon fiber, and the method of high-temperature dispersion stirring and injection molding Prepare a ceramic core, remove the pre-set cavity sandwich after sintering, and obtain a ceramic core with an embedded cavity structure.
The smoothness of the inner cavity surface of the ceramic core is significantly improved, the process steps are simplified, the production cycle is shortened, and the production cost is reduced.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic core preparation, and in particular relates to a ceramic core with an embedded cavity structure, a pre-cavity sandwich and a preparation method of slurry thereof. Background Art
[0002] The structure of the ceramic core with an embedded cavity structure is relatively complex. Chinese patent CN104014737 discloses a preparation process for a ceramic core with a complex embedded cavity structure, which uses a metal core as a pre-set cavity sandwich, puts the metal core into a ceramic core mold, and uses an injection molding method to prepare a ceramic core blank; then uses an electrolytic corrosion method to remove the metal core, and then puts it into a sintering furnace for sintering, and finally obtains a ceramic core with an embedded cavity structure. However, it is difficult to completely remove the metal core through electrocorrosion, resulting in a rough inner cavity of the ceramic core product with poor smoothness. Summary of the invention
[0003] In order to overcome the deficiencies of the prior art, the present invention provides a method for preparing a cavity sandwich slurry, a pre-set cavity sandwich, and a ceramic core with an embedded cavity structure. The technical solution provided by the present invention includes:
[0004] A method for preparing a cavity sandwich slurry, comprising:
[0005] The material components of the slurry include: 50wt% to 70wt% of polyethylene glycol, 20wt% to 30wt% of graphite powder, 0.5wt% to 1wt% of chopped nylon fiber, 4wt% to 16wt% of quartz glass powder, and the balance is stearic acid; wherein the parameters of the material components are: the average molecular weight of polyethylene glycol is 2000 to 6000, the particle size of graphite powder is 200 mesh to 800 mesh, the length of chopped nylon fiber is 0.5mm; the particle size of quartz glass powder is 325 mesh;
[0006] S1, mixing the above-mentioned graphite powder, quartz glass powder and chopped nylon fiber to form a premix for standby use;
[0007] S2. Add the above-mentioned polyethylene glycol, stearic acid and premix into a high-temperature dispersing mixer, disperse and stir at a temperature of 70-80° C. for 4 hours to obtain a cavity sandwich slurry.
[0008] Further, in S1, graphite powder, quartz glass powder and chopped nylon fibers are mixed in a ball mill to form a premix.
[0009] Furthermore, in S2, polyethylene glycol and stearic acid are first poured into a high-temperature dispersing mixer in sequence and heated until completely melted, the heating temperature being 70-80° C.; and then the premix is added into the high-temperature dispersing mixer for dispersion and stirring.
[0010] Alternatively, in S2, polyethylene glycol is first poured into a high-temperature dispersing mixer and heated to be completely melted at a heating temperature of 70-80° C.; and then stearic acid and the premix are added into the high-temperature dispersing mixer and dispersed and stirred.
[0011] Furthermore, the method further includes S3, transferring the cavity sandwich slurry obtained in S2 into a material cylinder of a hot pressing machine for standby use.
[0012] The method for preparing a preset cavity sandwich comprises: adding the cavity sandwich slurry prepared by the above method into the material cylinder of a hot pressing machine, and injecting it into a cavity sandwich mold by injection molding to obtain a corresponding preset cavity sandwich.
[0013] Furthermore, the injection molding parameters are: injection temperature is 80°C to 100°C, and holding time is 15 to 45s.
[0014] A method for preparing a ceramic core with an embedded cavity structure comprises:
[0015] Step 1: prepare ceramic core slurry, and then transfer the ceramic core slurry into a hot press;
[0016] Step 2: Place the preset cavity core into the corresponding position of the ceramic core forming mold, and inject the ceramic core slurry into the ceramic core forming mold through a hot press machine by injection molding to obtain a ceramic core blank; at this time, the corresponding position of the internal cavity structure of the ceramic core blank is currently occupied and filled by the corresponding preset cavity core;
[0017] Step 3: degreasing and sintering the ceramic core blank, and after the preset cavity sandwich is burned out, a ceramic core with an embedded cavity structure is obtained.
[0018] Furthermore, in step 3, the sintering temperature is 1200-1240° C. More preferably, the sintering temperature is 1220° C.
[0019] Further, the raw materials for preparing the ceramic core slurry include: paraffin-based plasticizer, ceramic powder, and mineralizer; first, quartz glass powder and mineralizer are pre-mixed in a three-dimensional motion mixer according to a proportion to obtain a premix; when preparing the slurry, the paraffin-based plasticizer is added to a high-temperature dispersing mixer and heated to melt, and after the plasticizer is completely melted, the premix is added to the mixing cylinder of the mixer, and after high-temperature dispersion and stirring, the ceramic core slurry is obtained, and after the dispersion and stirring are completed, the slurry is transferred to a hot press machine according to an injection molding process for standby use;
[0020] Furthermore, the paraffin-based plasticizer is a mixture of one or more of paraffin, beeswax, low-density polyethylene and stearic acid.
[0021] Furthermore, the mineralizer is made of any one of mullite powder and zirconium silicate powder or a mixture of the two.
[0022] Furthermore, the quartz glass powder is a mixture of one or more of 200-mesh quartz glass powder, 325-mesh quartz glass powder, and 800-mesh quartz glass powder.
[0023] Furthermore, the premixing time of the quartz glass powder and the mineralizer in the three-dimensional motion mixer is 12 hours.
[0024] Furthermore, the premix is added to the high-temperature dispersing mixer at a dispersing and stirring parameter of 90°C to 130°C and a stirring speed of 500rpm to 2500rpm. More preferably, the equipment temperature is 115°C and the dispersing and stirring speed is 1500rpm;
[0025] Furthermore, the premix is added to the high-temperature dispersing mixer and the dispersing and stirring time is 4 to 8 hours. More preferably, the dispersing and stirring time is 6 hours.
[0026] The ceramic core blank with an embedded cavity structure in the present invention is fired together with a preset cavity core in its cavity, and the preset cavity core is burned off to obtain a ceramic core with an embedded cavity structure. The surface smoothness of the cavity inner wall is better, which meets the demand for precision molding of complex cooling cavity structure products, simplifies the process steps, significantly shortens the production cycle, and reduces production costs. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0028] Example 1
[0029] Preparation of cavity sandwich slurry:
[0030] 50wt% of polyethylene glycol with an average molecular weight of 2000, 30wt% of 1000 mesh graphite powder, 16wt% of 325 mesh quartz glass powder, 1wt% of chopped nylon fiber, and the balance is stearic acid. Before preparing the sandwich slurry, the graphite powder, quartz glass powder and chopped nylon fiber are premixed in a ball mill for 4 hours to obtain a premix;
[0031] Pour polyethylene glycol and stearic acid into a high-temperature disperser at 70°C in sequence until completely melted, then add the premix into the high-temperature disperser and disperse and stir for 4 hours to obtain the cavity sandwich slurry. After the dispersion and stirring, transfer the sandwich slurry into the material cylinder of the hot press machine for standby use.
[0032] Forming of pre-set cavity sandwich:
[0033] The cavity sandwich slurry in the hot press cylinder is injected into the cavity sandwich mold by injection molding to obtain a preset cavity sandwich. The injection molding parameters are: injection temperature 80°C, holding time 45s;
[0034] Ceramic core slurry preparation:
[0035] Weigh 24wt% paraffin-based plasticizer, 5wt% mullite mineralizer, and 71wt% quartz glass powder by mass percentage, of which 200-mesh quartz glass powder and 800-mesh quartz glass powder account for 48wt% and 23wt% respectively. The paraffin-based plasticizer is composed of paraffin, beeswax, and stearic acid, and the ratio of the three components is 90:8:2. First, put the mullite powder and quartz glass powder into a three-dimensional motion mixer and mix for 12 hours to obtain a premix; then mix the paraffin, beeswax and stearic acid in a 70°C high-temperature disperser and heat until they are completely melted, and then add the premix to the high-temperature disperser. Turn on the equipment for dispersion and stirring, and disperse and stir for 8 hours at 115°C and 1500rpm to obtain the ceramic core slurry. Then transfer the slurry into the hot press according to the ceramic core preparation process requirements;
[0036] Forming of ceramic core blank: embed the preset cavity core into the corresponding position of the ceramic core forming mold, inject the ceramic core slurry into the ceramic core mold by injection molding to obtain a ceramic core blank embedded with the burnable preset cavity core.
[0037] Degreasing and sintering of ceramic core blanks: burying the ceramic core blanks in a sagger filled with alumina powder and sending them to a high-temperature roasting furnace with a sintering temperature of 1200°C for sintering; after the preset cavity sandwich is burned off, a ceramic core with an embedded cavity structure is obtained.
[0038] Example 2
[0039] Preparation of cavity sandwich slurry:
[0040] 70wt% of polyethylene glycol with an average molecular weight of 6000, 20wt% of 200-mesh graphite powder, 4wt% of 325-mesh quartz glass powder, 0.5wt% of 0.5mm short-cut fiber, and the balance is stearic acid.
[0041] Premixing graphite powder, quartz glass powder and chopped nylon fibers in a ball mill to obtain a premix;
[0042] Pour polyethylene glycol into a high-temperature dispersing mixer at a temperature of 80°C until it is completely melted, then add stearic acid and the premix into the high-temperature dispersing mixer in sequence, disperse and stir for 4 hours to obtain a cavity sandwich slurry; after the dispersion and stirring is completed, transfer the cavity sandwich slurry into the cylinder of a hot press machine for standby use;
[0043] Forming of pre-set cavity sandwich:
[0044] The sandwich slurry in the hot pressing machine cylinder is injected into the sandwich mold by injection molding to obtain a preset cavity sandwich. The injection molding parameters of the preset cavity sandwich are: injection temperature 100°C, holding time 15s;
[0045] Preparation of ceramic core slurry:
[0046] Weigh 16wt% paraffin-based plasticizer, 15wt% zirconium silicate powder, and 69wt% quartz glass powder by mass percentage, of which 200-mesh quartz glass powder and 325-mesh quartz glass powder account for 40wt% and 29wt% respectively. The paraffin-based plasticizer is composed of paraffin, beeswax, and low-density polyethylene, and the ratio of the three components is 90:7:3. Put the zirconium silicate powder and quartz glass powder into a three-dimensional motion mixer and mix for 12 hours to obtain a premix; mix the paraffin, beeswax and low-density polyethylene in a 70°C high-temperature disperser and heat until they are completely melted, then add the premix to the high-temperature disperser and start the equipment for dispersion and stirring. Disperse and stir at 115°C and 1500rpm for 8 hours to obtain the ceramic core slurry, and then transfer the slurry into the hot press according to the ceramic core preparation process requirements;
[0047] Forming of ceramic core blank: same as in Example 1;
[0048] Degreasing and sintering of ceramic core blank:
[0049] The ceramic core blank is buried in a sagger filled with alumina filler, and sent to a high-temperature roasting furnace with a sintering temperature of 1240°C for sintering; after the preset cavity sandwich is burned off, a ceramic core with an embedded cavity structure is obtained.
[0050] Example 3
[0051] Preparation of cavity sandwich slurry:
[0052] 60wt% of polyethylene glycol with an average molecular weight of 4000, 25wt% of 600-mesh graphite powder, 10wt% of 325-mesh quartz glass powder, 0.7wt% of 0.5mm short-cut fiber, and the balance is stearic acid.
[0053] Premixing graphite powder, quartz glass powder and chopped nylon fibers in a ball mill to obtain a premix;
[0054] Pour polyethylene glycol into a high-temperature dispersing mixer at a temperature of 75°C until it is completely melted, then add stearic acid and the premix into the high-temperature dispersing mixer in sequence, disperse and stir for 4 hours to obtain a cavity sandwich slurry; after the dispersion and stirring is completed, transfer the cavity sandwich slurry into the cylinder of a hot press machine for standby use;
[0055] Forming of pre-set cavity sandwich:
[0056] The cavity sandwich slurry is injected into the sandwich mold by injection molding to obtain the preset cavity sandwich. The injection molding parameters of the preset cavity sandwich are: injection temperature 90℃, holding time 30s;
[0057] Preparation of ceramic core slurry:
[0058] Weigh 20wt% paraffin-based plasticizer, 4wt% zirconium silicate powder, 5wt% mullite mineralizer, and 71wt% quartz glass powder by mass percentage, of which 200-mesh, 325-mesh, and 800-mesh quartz glass powder account for 28wt%, 20wt%, and 23wt%, respectively. The paraffin-based plasticizer is composed of paraffin, beeswax, and stearic acid, and the mass percentages of the three components are 90wt%:8wt%:2wt%. Put mullite powder, zirconium silicate powder, and quartz glass powder into a three-dimensional motion mixer and mix for 12 hours to obtain a premix. Mix and heat paraffin, beeswax, and stearic acid in a 70°C high-temperature disperser until they are completely melted, and then add the premix to the high-temperature disperser. Turn on the equipment for dispersion and stirring, and disperse and stir at 115°C and 1500rpm for 8 hours to obtain the ceramic core slurry. Then transfer the slurry into the hot press according to the ceramic core preparation process requirements;
[0059] Forming of ceramic core blank: same as in Example 1;
[0060] Degreasing and sintering of ceramic core blank:
[0061] The ceramic core blank is buried in a sagger filled with alumina filler and sent to a high-temperature roasting furnace with a sintering temperature of 1220℃ for sintering.
[0062] The inner cavity surface roughness and product qualification rate of the ceramic core with inner cavity structure prepared in the above embodiments are shown in the following table. It can be found that the ceramic core product prepared by the present invention has good inner cavity surface roughness, and the product qualification rate is above 75% on average.
[0063] Example Surface roughness of core cavity Product qualification rate 1 0.074 75% 2 0.052 83% 3 0.086 73%
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a cavity sandwich slurry, characterized in that: include: The material components of the slurry include: 50wt% to 70wt% of polyethylene glycol, 20wt% to 30wt% of graphite powder, 0.5wt% to 1wt% of chopped nylon fiber, 4wt% to 16wt% of quartz glass powder, and the balance is stearic acid; wherein the parameters of the material components are: the average molecular weight of polyethylene glycol is 2000 to 6000, the particle size of graphite powder is 200 mesh to 800 mesh, the length of chopped nylon fiber is 0.5mm; the particle size of quartz glass powder is 325 mesh; S1, mixing the above-mentioned graphite powder, quartz glass powder and chopped nylon fiber to form a premix for standby use; S2. Add the above-mentioned polyethylene glycol, stearic acid and premix into a high-temperature dispersing mixer, disperse and stir at a temperature of 70-80° C. for 4 hours to obtain a cavity sandwich slurry.
2. The method for preparing the cavity sandwich slurry according to claim 1, characterized in that: In S1, graphite powder, quartz glass powder and chopped nylon fibers are mixed in a ball mill to form a premix.
3. The method for preparing the cavity sandwich slurry according to claim 1, characterized in that: In S2, polyethylene glycol and stearic acid are first poured into a high-temperature dispersing mixer in sequence and heated until completely melted, the heating temperature being 70-80° C.; and then the premix is added into the high-temperature dispersing mixer for dispersion and stirring.
4. The method for preparing the cavity sandwich slurry according to claim 1, characterized in that: In S2, polyethylene glycol is first poured into a high-temperature dispersing mixer and heated to be completely melted at a heating temperature of 70-80° C.; then stearic acid and the premix are added into the high-temperature dispersing mixer and dispersed and stirred.
5. The method for preparing the cavity sandwich slurry according to claim 1, characterized in that: The process also includes S3, transferring the cavity sandwich slurry obtained in S2 into a material cylinder of a hot pressing machine for standby use.
6. A method for preparing a pre-cavity sandwich, comprising: The cavity core sandwich slurry prepared by the preparation method of the cavity core sandwich slurry according to claim 1 is added into the cylinder of a hot pressing machine, and injected into a cavity core sandwich mold by injection molding to obtain a corresponding preset cavity core sandwich.
7. The method for preparing a pre-cavity sandwich according to claim 6, characterized in that: Injection molding parameters are: injection temperature is 80℃~100℃, and holding time is 15~45s.
8. A method for preparing a ceramic core with an embedded cavity structure, comprising: Step 1: prepare ceramic core slurry, and then transfer the ceramic core slurry into a hot press; Step 2: Place the pre-cavity core prepared by the method for preparing the pre-cavity core according to claim 6 into the corresponding position of the ceramic core forming mold, and inject the ceramic core slurry into the ceramic core forming mold by a hot press machine using an injection molding method to obtain a ceramic core blank; at this time, the corresponding position of the internal cavity structure of the ceramic core blank is currently occupied and filled by the corresponding pre-cavity core; Step 3: degreasing and sintering the ceramic core blank, and after the preset cavity sandwich is burned out, a ceramic core with an embedded cavity structure is obtained.
9. The method for preparing a ceramic core with an embedded cavity structure according to claim 8, characterized in that: In the step three, the sintering temperature is 1200-1240°C.
10. The method for preparing a ceramic core with an embedded cavity structure according to claim 8, characterized in that: The raw materials for preparing ceramic core slurry include: paraffin-based plasticizer, ceramic powder, and mineralizer; first, quartz glass powder and mineralizer are charged into a three-dimensional motion mixer in proportion to obtain a premix; when preparing the slurry, the paraffin-based plasticizer is added into a high-temperature dispersing mixer and heated to melt, and after the plasticizer is completely melted, the premix is added into the mixing cylinder of the mixer, and after high-temperature dispersion and stirring, the ceramic core slurry is obtained, and after the dispersion and stirring are completed, the slurry is transferred to a hot pressing machine according to the injection molding process for standby use.
Citation Information
Patent Citations
Fiber reinforced ceramic core
CN104072181A
Silicon oxide-based ceramic core for large-size directional hollow blade of heavy-duty gas turbine and preparation of silicon oxide-based ceramic core
CN114249588A
Sintering preparation method of high-strength mechanical property silicon-based ceramic core
CN114656248A
Porous ceramic sandwich injection molding method and device
CN116460956A
Precision casting process method of steam valve part
CN117620081A